ANALISIS SEMIOTIKA CHARLES SANDERS PIERCE TERHADAP KERUKUNAN SOSIAL DALAM BUDAYA MAKAN SETELAH KHATAMAN AL-QUR'AN PADA KELOMPOK TAHFIDZ DI BOJONEGORO - Nurul Musyafa’ah; Aya Mamlu’ah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Reading the Qur'an is a noble practice that is recommended to every Muslim. So it is not surprising that in all corners of the world also persistently enliven the activities of reading the Qur'an with several models. One of them is with the model of the qur'an simultaneously. These activities can become a shiyiar of Islam by providing additional spirit in reading and mentadabburi al-Qur'an. The series of problem formulations that guide the implementation of research, presented with the following questions: 1. How is the analysis of Charles Sanders Pierce's Theory of Social Harmony in Eating Culture After the Qur'anic Khataman in the Tahfidz Group in Bojonegoro? 2. What is the Meaning of Charles Sanders Pierce's Theoretical Analysis Representation of Social Harmony in Eating Culture After the Qur'anic Recitation in the Tahfidz Group in Bojonegoro? The research methodology used is to use a qualitative-descriptive approach to analytics. The instrument used for data collection is direct observation, namely by prioritizing the role and presence of researchers to the location directly, interviews, and documentation. The results of this study showed that the culture of eating after the qur'an was able to add its own ni'mat taste to the worship of the qur'an.